Efektifitas Telemedicine Pada Pengobatan Tuberculosis Pada Negara Berpenghasilan Menengah ke Bawah: Systematic Review - Triana, Rosselini; Pujiyanto, Pujiyanto; Chandra, Erfan (J-KESMAS: Jurnal Kesehatan Masyarakat, 2023)
Tuberculosis (TB) is one of the major health issues worldwide, with a significant number of cases and deaths in countries with high TB prevalence. Telemedicine is being used to improve diagnosis, treatment, and public health. We aimed to explore the effectiveness of telemedicine in TB treatment in Low- and Middle-Income Countries (LMIC). The study used a systematic literature review, using relevant keywords and inclusion criteria, and searched papers written in English between 2014 and 2023 from PubMed, Cochrane, and Embase databases. For inclusion, titles and abstracts were screened using PRISMA. From 849 studies, we found 13 studies fit the inclusion criteria. Telemedicine gives varying results on treatment success, patient compliance, and prevention of loss to follow-up. Mostly, the results are better but insignificant. Telemedicine facilitates the detection of TB cases, improves knowledge of TB, and improves patient-health worker relationships. In conclusion, telemedicine may be a promising approach to improving the effectiveness of TB treatment despite intervention effects being found to vary between one and each study. Advanced research is needed to evaluate the more optimum and wider implementation of telemedicine.